2009
DOI: 10.1097/pdm.0b013e3181857e92
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thawing on RNA Integrity and Gene Expression Analysis in Fresh Frozen Tissue

Abstract: Biobanks of fresh, unfixed human tissue represent a valuable source for gene expression analysis in translational research and molecular pathology. The aim of this study was to evaluate the impact of thawing on RNA integrity and gene expression in fresh frozen tissue specimens. Portions of snap frozen tonsil tissue, unfixed or immersed in RNAlater, were thawed at room temperature for 0 minute, 5 minutes, 30 minutes, 45 minutes, 1 hour, 3 hours, 6 hours, and 16 hours before RNA extraction. Additionally, tonsil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 25 publications
4
69
0
Order By: Relevance
“…Noteworthy is the inclusion of patient performance status, a parameter not annotated in previous datasets. Histopathologic review, fresh-frozen tissue handling, selection of representative tissue with high tumor cell content, and mRNA extraction were conducted using uniform and standardized protocols within the infrastructure of an established biobank and a diagnostic molecular pathology laboratory (20)(21)(22)(23). Thus, we believe that artifacts due to poor tissue quality and methodologic inconsistencies have been minimized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy is the inclusion of patient performance status, a parameter not annotated in previous datasets. Histopathologic review, fresh-frozen tissue handling, selection of representative tissue with high tumor cell content, and mRNA extraction were conducted using uniform and standardized protocols within the infrastructure of an established biobank and a diagnostic molecular pathology laboratory (20)(21)(22)(23). Thus, we believe that artifacts due to poor tissue quality and methodologic inconsistencies have been minimized.…”
Section: Discussionmentioning
confidence: 99%
“…All fresh-frozen tissue samples were collected using the same standardized protocol (20)(21)(22)(23), and each frozen section was reviewed by pathologists (P. Micke and J. Botling) to confirm that the sample contained representative tumor tissue.…”
Section: Patients and Tissue Samplesmentioning
confidence: 99%
“…Keeping tissue frozen until homogenization in a solution containing RNase inhibitors ensures consistent results by preventing inconsistent thawing of samples, which leads to differential RNA degradation [Botling et al, 2009;Huang et al, 2013;Kirschner et al, 2013]. Some labs remove tissue samples from -80 ° C storage, transport them on blue ice and then proceed to homogenize samples and extract the RNA using a wide variety of techniques, during which the samples may begin to thaw prior to RNA extraction.…”
Section: Rna Isolation: Maintain the Cold Chain With Frozen Samples Pmentioning
confidence: 99%
“…Neither freezing and thawing nor storage of frozen tissue affected RNA in muscle cell nuclei of larvae of Walleye Pollock in our study. For frozen human tissue, no signifi cant RNA degradation (as measured by gene expression and electropherograms) was detected after 16 h on ice (Micke et al, 2006), and another study showed that signifi cant RNA degradation did not begin until 30 min after thawing at room temperature (Botling et al, 2009). Although those studies did not measure the amount of RNA present, they do support our assertion that the protocol used in our study was adequate to preserve RNA because larvae were frozen quickly, thawed tissue was kept cool on ice, and the time from tissue thawing to analysis with fl ow cytometry was typically not longer than 5 h. Our results differ from the fi ndings of Theilacker and Shen (1993b) in that their study indicated that a cryoprotectant and acid were needed before freezing to stabilize RNA in brain cells of larvae of Walleye Pollock.…”
Section: Control Modelmentioning
confidence: 99%